The Impact of Competitive Sports on the Mental Health of Young People - Józefiak, Maciej; Sobkiewicz, Piotr; Niekurzak, Karolina; Jędrak, Maciej; Flis, Blanka (Quality in Sport, 2024)
Introduction Mental health is a crucial component of overall well-being for everyone, and it becomes particularly important in the context of young student-athletes who must simultaneously meet educational and athletic challenges. Athletes, like their peers, struggle with various mental health issues such as anxiety, depression, suicidal thoughts, eating disorders, sleep deficits, burnout, and overtraining. The additional activity of engaging in competitive sports, compared to those who do not, can exacerbate these symptoms. The aim of study Identify and analyze specific sources of stress and mental health issues among young student-athletes and young individuals. Compare different research groups. Conclusion Student-athletes face the unique challenge of balancing intense training and sports competitions with educational demands. The constant pursuit of peak performance and coping with high expectations can lead to significant psychological stress. Factors such as injuries, overtraining, social identity issues, and sleep problems further impact their mental health, often leading to the development or worsening of existing mental health issues. It is important to note that professional psychological care is essential in managing the training schedule of a young athlete. For their development to be balanced across various dimensions such as proper physical growth, well-being, and mental wellness, this support is crucial.